Konservasi Air dan Energi dengan Menghidupkan Sunnah Nabi - Ahmad, Mujahidin (Department of Biology Science and Technology Faculty UIN Maulana Malik Ibrahim Malang, 2013)
Islam is a universal religion. Not only governs the relationship between servant and God but also regulates the relationship with fellow beings. Among the teachings of Islam that governs the relationship with the creatures is how the adherents of Islam set to be considerate of the environment, ie, how should humans maintain balance of nature and not ruin it. The use of water and energi, including matters governed by Islam through the Qur'an and the instructions Prophet Sallallaahu 'alaihi wasallam. Instructions regarding the procedure of which the Prophet made ablution, bathing, brushing teeth closely related to water conservation, while the doctrine of fasting, to walk to the mosque, turn off a light during sleep so strongly associated with the doctrine of the conservation of energy. By following the Sunnah of a Moslem not only to be rewarded, but also contribute to the conservation of natural resources whose benefits will be felt by all mankind